Driven from work: Graduated driver license programs and teen labor market outcomes - Laura M. Argys; Thomas A. Mroz; M. Melinda Pitts (Federal Reserve Bank of Atlanta, 2019)
In response to a high incidence of motor vehicle accidents among teens, states have adopted policies that broadly mandate restrictions on novice teen drivers, including more prelicensure education and supervised driving as well as postlicensure curfews and restrictions on the number of passengers. By making it costlier to obtain a driver's license and reducing the benefits of a license by limiting driving hours and restricting passengers, graduated driver licensing (GDL) may also alter the cost of activities that are complementary to driving. This research explores the unintended consequences GDL laws may have on the labor/leisure tradeoff of teens, as it alters the return to market work and the benefit of leisure. The results suggest that approximately half of the decline in teen labor force participation since 1995 can be attributed to the restrictions associated with graduated driver licenses.
Keywords: J22; I18; H7; 330; graduated driver licensing; teen labor force participation; driving restriction